1997
DOI: 10.1002/mds.870120611
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopy in parkinson's disease and atypical parkinsonian disorders

Abstract: Proton magnetic resonance spectroscopy (1H-MRS), localized to the lentiform nucleus, was carried out in 12 patients with idiopathic Parkinson's disease (IPD), seven patients with multiple-system atrophy (MSA), seven patients with progressive supranuclear palsy (PSP), and 10 healthy age-matched controls. The study assessed the level of N-acetylaspartate (NAA), creatine-phosphocreatine (Cr), and choline (Cho) in the putamen and globus pallidus of these patients. NAA/Cho and NAA/Cr ratios were significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 36 publications
2
40
1
1
Order By: Relevance
“…Proton magnetic resonance spectroscopy of the striatum has provided variable results in PD itself, but this technique may be useful for differentiating between PD and atypical parkinsonian syndromes, such as multiple system atrophy or progressive supranuclear palsy [13][14][15][16], and there may also be changes in the posterior cingulate [17] and presupplementary motor area cortex [18]. Phosphorus spectroscopy may also reveal changes that appear to differ between PD and multiple system atrophy [19,20].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Proton magnetic resonance spectroscopy of the striatum has provided variable results in PD itself, but this technique may be useful for differentiating between PD and atypical parkinsonian syndromes, such as multiple system atrophy or progressive supranuclear palsy [13][14][15][16], and there may also be changes in the posterior cingulate [17] and presupplementary motor area cortex [18]. Phosphorus spectroscopy may also reveal changes that appear to differ between PD and multiple system atrophy [19,20].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The NAA/Cho and NAA/Cr ratios were significantly reduced in the putamen and globus pallidus of MSA and the PSP patients, in which neuronal loss involves, compared with the control subjects (Federico et al, 1997). In another study Federico at al.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 87%
“…Other 1 H-MRS examinations didn't show significant difference between the PD patients and the control subjects (Tedeschi et al, 1997), also in the striatum (Holshouser et al, 1995), in the putamen and globus pallidus (Federico et al, 1997), and in occipital lobe (Bowen et al, 1995). The NAA/Cho and NAA/Cr ratios were significantly reduced in the putamen and globus pallidus of MSA and the PSP patients, in which neuronal loss involves, compared with the control subjects (Federico et al, 1997).…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 96%
“…However, contradictory results for the NAA/Cr ratio in the frontal cortex have been reported in parkinsonian syndromes subjects (Abe et al., 2000). In addition, some studies showed no significant difference in Cho/Cr ratio in the lentifom nucleus between PD patients and healthy controls (Federico et al., 1997), which may result from regional and individual variability or different signal‐to‐noise ratio in different brain structures. Consequently, an overall description of the metabolic status in multiple regions of the brain is needed.…”
Section: Introductionmentioning
confidence: 99%